MICROESTRUTURA E TEXTURA CRISTALOGRÁFICA DOS AÇOS INOXIDÁVEIS MARTENSÍTICOS AISI 410, AISI 420 e EM 1.14116 - Moura, Ariane Neves de (2022)
Martensitic transformation in martensitic stainless steel occurs only after the final conformation in the quenching process. Ferrite grains and Cr-rich carbides are observed in the microstructure during the hot rolling, cold rolling and annealing industrial processes. In this context, this study investigated the microstructures and textures of AISI 410, AISI 420 and EN 1.4116 stainless steels with different carbide fractions, initial grain sizes and textures after 50 % cold rolling reduction and annealing. Analysis of the experimental results showed the initial texture influenced the intensity and existence of texture gradient in the recrystallized samples. The stored energy after cold rolling and grain growth during annealing were mainly influenced by the (Cr,Fe)23C6 carbide fraction, which was identified as Cr15.58Fe7.42C6 type. Reducing initial grain size caused a change in the deformation mode to larger grain boundary constraints, weakening the {110}<001> Goss component in recrystallized textures. The recrystallized microstructures of AISI 420 and EN 1.4116 steels were heterogeneous owing to the (Cr,Fe)23C6 carbide bands in the as-received condition. In addition, the selective particle drag caused the γ- steels.